(untitled) (Nepalese Journal of Cancer, 2026)
Introduction: Cancer is a leading cause of morbidity, and chemotherapy remains a principal treatment. Its effectiveness depends on patients’ understanding of the treatment and self-care practices. The study aimed to find out the level of knowledge, attitude, and practice regarding chemotherapy among cancer patients attending a tertiary care center. Methods: A descriptive cross-sectional study was conducted at a tertiary care hospital in Chitwan, Nepal, from January 2024 to June 2024. Ethical clearance was obtained from the Institutional Review Committee. A convenience sampling method was used to select 110 participants. Data was entered into Microsoft Excel 2016 and analyzed using the Statistical Package for the Social Sciences version 20.0. Point estimate at 95% Confidence Interval was calculated along with frequency and percentages for binary data and mean and standard deviation for continuous data. Results: Out of 110 participants, 90 (81.82%) had a poor level of knowledge regarding chemotherapy. The mean ± SD was 44.49 ± 14.39 years. Regarding attitude, 74 (67.27%) maintained a neutral attitude, while 58 (52.73%) completely agreed with the need for health education. For practice, 67 (60.91%) demonstrated poor self-care practices, and follow-up to the hospital on time was observed in 109 (99.09%). Conclusions: Patients receiving chemotherapy demonstrated low knowledge and poor self-care practices, despite maintaining a neutral attitude and expressing a strong willingness to receive health education.